Work Stress and Its Impact on Employee Performance, Turnover, and Absenteeism: A Comprehensive Study at E & E Manufacturing - Hasan Saleh; Nur Syuhada Shahidan (Master of Management Department, Faculty of Economics, Universitas Bangka Belitung, 2023)
In today’s diverse business landscape, the pervasive challenge of stress affects individuals across various sectors. This study, employing a quantitative research approach, explores the multifaceted nature of work stress, investigating its dual impact on individuals and organizations. Specifically, it scrutinizes the intricate relationship between work stress and organizational dynamics, concentrating on identified factors contributing to diminished employee performance. Utilizing a sample size of 80 participants from XYZ Industries, a manufacturing company in Ayer Keroh, Melaka, Malaysia, the research employs SPSS version 20 for data analysis. The study further delves into the consequences of stress on employee performance, manifested through absenteeism and turnover. The findings highlight the substantial influence of employee performance on the overall organizational effect, underscoring the pivotal role of a healthy work environment. Furthermore, turnover emerges as a significant factor shaping organizational dynamics, emphasizing the necessity of addressing challenges associated with turnover. These insights contribute to a nuanced understanding of stress-related challenges within organizational contexts, offering actionable recommendations to navigate these complexities effectively.